Central European Vaccination Advisory Group (CEVAG) guidance statement on recommendations for the introduction of HPV vaccines - Prymula, Roman; Anca, Ioana; André, Francis; Bakir, Mustafa; Czajka, Hanna; Lutsar, Irja; Mészner, Zsófia; Salman, Nuran; Simurka, Pavol; Usonis, Vytautas (European journal of pediatrics, 2009)
Vaccines against human papillomavirus (HPV), the primary causative agent in cervical cancer, are licensed. This paper contains the Central European Vaccination Advisory Group (CEVAG) guidance statement on the introduction of HPV vaccines in central Europe. Eight countries currently have medical representatives on CEVAG: the Czech Republic, Estonia, Hungary, Lithuania, Poland, Romania, Slovakia and Turkey. By raising awareness and disseminating information, CEVAG aims to promote the efficient and safe use of vaccines to prevent, control and if possible eliminate infectious diseases. In January 2008, the European Centre for Disease Prevention and Control published a report entitled Guidance for the Introduction of HPV Vaccines in EU Countries. Members of CEVAG have taken the information relevant to their countries from this report and, with consideration of local issues, produced these guidance recommendations for the introduction of HPV vaccines in the CEVAG region, which may be adapted for use in individual countries.
Keywords: vakcíny proti papilomavirům; vakcinace; Humans; poradní výbory; dítě; Vaccination; Child; Female; Advisory Committees; mladý dospělý; dospělí; nádory děložního čípku; lidé; Europe; Adult; Papillomavirus Infections; ženské pohlaví; Male; analýza nákladů a výnosů; Adolescent; infekce papilomavirem; Uterine Cervical Neoplasms; Young Adult; Papillomavirus Vaccines; mužské pohlaví; Cost-Benefit Analysis; Evropa; mladiství